2020
DOI: 10.2174/1874467213666200212102710
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of the Food-Derived Hydrophilic Antioxidant Ergothioneine Enhances Object Recognition Memory in Mice

Abstract: Background: The enhancement of learning and memory through food-derived ingredients is of great interest to healthy individuals as well as those with diseases. Ergothioneine (ERGO) is a hydrophilic antioxidant highly contained in edible golden oyster mushrooms (Pleurotus cornucopiae var. citrinopileatus), and systemically absorbed by its specific transporter, carnitine/organic cation transporter OCTN1/SLC22A4. Objective: This study aims to examine the possible enhancement of object recognition memory by oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…ET has a wide range of unique properties, conferring a variety of cytoprotective capabilities which, amongst others, includes the ability to scavenge reactive oxygen and reactive nitrogen species (ROS/RNS) such as hydroxyl radicals ( • OH) [ 33 ], hypochlorous acid (HOCl) [ 33 ], singlet oxygen ( 1 O 2 ) [ 34 , 35 ], and peroxynitrite (ONOO − ) [ 36 ]. However, a wide range of other studies have demonstrated that ET can, amongst other things, modulate inflammation [ 37 , 38 , 39 ], chelate divalent metal cations such as iron and copper (thereby decreasing the ability of these metal ions to stimulate oxidative damage) [ 33 , 40 , 41 , 42 ], protect against UV radiation-induced damage [ 43 , 44 ], inhibit expression of vascular adhesion proteins [ 45 , 46 ], inhibit myeloperoxidase activity [ 47 ], protect against the phagocyte respiratory burst [ 48 , 49 ], induce the expression of heat shock protein-70 [ 39 , 50 ], promote neuronal differentiation [ 51 , 52 , 53 ], and prevent lung [ 54 ] and liver [ 55 , 56 ] fibrosis. These features of ET and their application against various pathological aspects of COVID-19 will be discussed in greater detail throughout this review to demonstrate the multifunctional capabilities of ET as a potential therapeutic for coronavirus infection.…”
Section: Biology Of Ergothioneinementioning
confidence: 99%
See 3 more Smart Citations
“…ET has a wide range of unique properties, conferring a variety of cytoprotective capabilities which, amongst others, includes the ability to scavenge reactive oxygen and reactive nitrogen species (ROS/RNS) such as hydroxyl radicals ( • OH) [ 33 ], hypochlorous acid (HOCl) [ 33 ], singlet oxygen ( 1 O 2 ) [ 34 , 35 ], and peroxynitrite (ONOO − ) [ 36 ]. However, a wide range of other studies have demonstrated that ET can, amongst other things, modulate inflammation [ 37 , 38 , 39 ], chelate divalent metal cations such as iron and copper (thereby decreasing the ability of these metal ions to stimulate oxidative damage) [ 33 , 40 , 41 , 42 ], protect against UV radiation-induced damage [ 43 , 44 ], inhibit expression of vascular adhesion proteins [ 45 , 46 ], inhibit myeloperoxidase activity [ 47 ], protect against the phagocyte respiratory burst [ 48 , 49 ], induce the expression of heat shock protein-70 [ 39 , 50 ], promote neuronal differentiation [ 51 , 52 , 53 ], and prevent lung [ 54 ] and liver [ 55 , 56 ] fibrosis. These features of ET and their application against various pathological aspects of COVID-19 will be discussed in greater detail throughout this review to demonstrate the multifunctional capabilities of ET as a potential therapeutic for coronavirus infection.…”
Section: Biology Of Ergothioneinementioning
confidence: 99%
“…ET has been suggested to play a role in neuronal differentiation and maturation, which may be involved in repair following brain injury [ 51 , 52 , 53 ]. Studies have demonstrated that exposure of cultured hippocampal neurons to ET elevated the expression of the synapse formation marker synapsin-1 and neurotrophin-3 and -5, and ET supplementation in mice was shown to enhance learning and memory (object recognition test) and increase the number of mature spines in the hippocampus [ 51 ]. This ability may be useful following viral infiltration and damage to neurons in the brain.…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, ET is present in human breast milk [ 47 ] and is also present in cow [ 53 ] and goat milk [ 47 ]. Nakamichi et al [ 54 ] and Ishimoto et al [ 55 ] demonstrated that ET promotes neurogenesis in mice, which may enhance memory [ 56 ], or alleviate symptoms of neuropsychiatric disorders [ 54 ]. It may therefore be plausible that ET plays a role in neuronal differentiation during growth and maturation of the brain in the developing child.…”
Section: A Gerontological Perspectivementioning
confidence: 99%